Protocol for a three-phase prospective study to develop educational resource of antimicrobial resistance and stewardship for medical programme - Dhaliwal, Jagjit Singh; Mohamad Yusra, Muhammad Adi Marhain; Muharram, Siti Hanna; Akkawi, Muhammad Eid; Hussain, Zahid; Rahman, Hanif; Yuh, Yen Kok; Dhaliwal, Sachinjeet Kaur Sodhi; Long, Chiau Ming (BMJ Publishing Group, 2022)
Introduction Antimicrobial resistance (AMR) is one of the critical medical issues of the 21st century. Medical professionals are the primary prescribers of antimicrobials; their undergraduate education of antimicrobial stewardship (AMS) is considered one of the fundamental approaches in combating the issue of AMR. This education level provides a platform to bridge any gaps in their knowledge and competency in AMS. This study aims to develop an educational resource on microbes, hygiene and prudent antimicrobial use for the undergraduate medical programme. The guideline produced will then be assimilated into the existing curriculum which will help to improve the quality of education which in turn will improve rationale as the use of antimicrobials in the future. Methods and analysis A three-step approach consensus approach will be adopted for this study for the development of a validated medical curriculum guideline on AMR. A preliminary curriculum for the programme will be drafted from reviews of published literature including syllabi as well as national and international guidelines. A total of 26 potential sources were found to be relevant, and selected for this study. Subsequently, the drafted curriculum will be subjected for validation via online surveys by various infectious disease experts. Finally, a Delphi technique will be employed to obtain consensus on heterogeneous fidings to the revised curriculum. The quantitative and qualitative responses will be analysed and discussed among the panel of researchers. Ethics and dissemination This study protocol has been approved by the Institute of Health Sciences Research Ethics Committee of Universiti Brunei Darussalam (Reference: UBD/PAPRSBIHSREC/2020/124). Informed consent declaration will be collected prior to data collections as indication of agreement of participation in the study. Results will be made available to medical educators and also researchers on AMR and stewardship. The results also will be disseminated at feedback sessions to offiers at Ministry of Health and Ministry of Education, Brunei Darussalam.